Chemistry Teachers’ Perceptions on STEM (Science, Technology, Engineering, and Mathematics) Education - Mardiyah, Farah Fathiaty; Saridewi, Nanda; Bahriah, Evi Sapinatul (Department of Science Education, Universitas Sultan Ageng Tirtayasa, 2021)
Perception is a process of using the knowledge that a person has in interpreting an object. This study aims to determine the perceptions of Islamic senior high school chemistry teachers in South Tangerang, Indonesia towards STEM (Science, Technology, Engineering, and Mathematics) education. This study used descriptive qualitative method. The instrument used was an online questionnaire containing 17 questions with opened and closed forms, then the results were analyzed using hermeneutic techniques. Based on the results, it can be concluded that Islamic senior high school chemistry teachers in South Tangerang, Indonesia have a perception that STEM education is needed in learning.